Karakteristik Gelatin Kulit Kaki Ayam dengan Perlakuan Tingkat Konsentrasi Asam Klorida - Devi Kumala Sari; Viny Suwita; Hajar Setyaji (Jurnal Teknologi Pengolahan Pertanian, 2020)
Gelatin is a protein from bone and skin collagen hydrolysis that is widely used for various industrial purposes, both in the food and non-food industries. Gelatin is used as an agent to increase elasticity, consistency and stability. Gelatin is usually obtained by acid or alkaline hydrolysis. This study aims to utilize the skin of chicken feet (Tarsometa tarsus) to produce the best quality and physicochemical properties of gelatin with hydrochloric acid treatment and as an alternative to halal gelatin. The design used was a completely randomized design (CRD) consisting of treatment of HCl concentration and 3 replications, namely 0.5%; 1.0%; 1.5%; 2.0%; 2.5% and 3.0%. The variables observed consisted of water content, ash content, protein content and yield. The data obtained from the observations were analyzed using analysis of variance at the 5% level. If it is significantly different, continue with Duncan's New Multiple Range Test (DNMRT) at the 5% level. The results of this study indicate that the concentration of HCl has a significant effect on yield, color and viscosity. HCl with the concentration of 1.5% is the best concentration with water content of 8.84%, ash content of 0.25%, protein content of 95.42%, yield of 8.89%.